Difference in hot carrier cooling rate between Langmuir–Blodgett and drop cast PbS QD films due to strong electron–phonon coupling. Issue 43 (31st October 2017) - Cao, Wenkai; Yuan, Lin; Patterson, Rob; Wen, Xiaoming; Tapping, Patrick C.; Kee, Tak; Veetil, Binesh Puthen; Zhang, Pengfei; Zhang, Zewen; Zhang, Qiuyang; Reece, Peter; Bremner, Stephen; et al.
Abstract : The carrier dynamics of lead sulphide quantum dot (PbS QD) drop cast films and closely packed ordered Langmuir–Blodgett films are studied with ultra-fast femtosecond transient absorption spectroscopy. Abstract : The carrier dynamics of lead sulphide quantum dot (PbS QD) drop cast films and closely packed ordered Langmuir–Blodgett films are studied with ultra-fast femtosecond transient absorption spectroscopy. The photo-induced carrier temperature is extracted from transient absorption spectra and monitored as a function of time delay. The cooling dynamics of carriers in PbS QDs suggest a reduction of the carrier energy loss rate at longer time delays through the retardation of the longitudinal optical (LO) phonon decay due to partial heating of acoustic phonon modes. A slowed hot carrier cooling time up to 116 ps is observed in the drop cast film. A faster cooling rate was also observed in the highly compact Langmuir–Blodgett film due to the enhanced carrier–LO phonon coupling strength arising from the Coulombic interaction in neighboring QDs, which is verified by temperature dependent steady state PL measurements.